Expression of selected pathogenesis-related proteins at early stage of Ganoderma boninense infection in Elaeis guineensis jacq. seedlings - Ramli, Redzyque Ramza (2019)
Basal stem rot (BSR) is the most devastating oil palm disease caused by Ganoderma boninense. It is only evident when the infection has progressed by 60–70% which is too late to cure the palm. Studies on early defense responses are required to provide insightful information on the initiation of defense signaling networks upon recognition of pathogen. Thus, information on early interactions of plant-pathogens is crucial to allow screening for detection of the potential threat of BSR, especially on young palms. This study was conducted to isolate and detect the presence of G. boninense within infected oil palm seedlings, and to identify the differentially expressed genes (DEGs) which related to pathogenesis (PR) as well as to analyse PR genes expression in oil palm roots as a result of oil palm-G. boninense interaction. Oil palm seedlings were artificially infected with G. boninense inoculums. Deoxyribonucleic acid (DNA) samples were taken from infected palms (T1) and G. boninense pure culture for detection using polymerase chain reaction (PCR), multiple sequence alignment (MSA) and basic local alignment search tool (BLAST) via NCBI. Polymerase chain reaction (PCR) and nested PCR produced amplicon with the expected size of 200 base pairs (bp) for 3 days post-inoculation (DPI) and G. boninense pure culture, as well as 100 bp for 7 and 11 DPI. MSA showed the presence of the conserved sequence and ≥95% identity generated via BLAST for all amplicons of T1 samples and G. boninense pure culture. Ribonucleic acid (RNA) samples were extracted from the root tissues at different periods (0, 3, 7, 11 DPI) and used for ribonucleic acid sequencing (RNASeq) analysis. DEGs were identified. DEGs analyses displayed that several PR proteins were expressed as a result of the defense mechanism of oil palm against G. boninense including chitinase 1 isoform X3 (EgChi1X3), germin-like 8-14 (EgGer8), glu S. griseus protease inhibitor (EgGluP), glucan endo-1,3-beta-glucosidase 3-like (EgGlu3) and subtilisin-like protease SBT1.9 (EgPro1.9). These genes were searched for primary structural homology via BLAST, based on size and exon count. Homology searches for selected PR genes with their respected PR groups generated. The conserved domain for each PR gene was analysed to determine their functions in terms of plant defense. MSA was done and generated a phylogenetic tree for each PR gene to check their related grouping based on the conserved domain. MSA generated ≥ 90% of primary structural homology among selected genes with their respected PR groups. Based on conserved domains, each PR gene function was determined which is related to plant defense. EgChi1X3 may be involved in the production of elicitor compounds and the degradation of fungal chitins. EgGer8 is probably involved in oxidative degradation of oxalate and preventing plant cell wall hydrolysis. EgGluP may be involved in promoting inhibition of pathogen proteolytic enzymes. EgGlu3 is possibly related directly to the activity of degradation and rendering fungal cell walls susceptible to plant responses and cell lysis. EgPro1.9 may be involved in extracellular protein secretion and mature peptide degradation. The defense response obtained from DEG analyses showed immense upregulation of EgChi1X3, EgGer8 and EgGluP with an average of 12, 3 and 32-fold higher than control at 3 DPI. While EgGlu3 and EgPro1.9 significantly expressed with 218 and 6-fold at 11 DPI when compared to control. The phylogenetic tree showed that the selected PR genes were clustered together with date palm due to probable motif similarity and sequence homology. Based on this study, these selected PR genes will be potential candidates in developing biomarkers for early phase detection of G. boninense infection.